MSH2 Gene Point Mutations Are Not Antifungal Resistance Markers in Candida glabrata - Bordallo-Cardona, María Ángeles (Antimicrob Agents Chemother, 2018)
The high rates of antifungal resistance in Candida glabrata may be facilitated by the presence of alterations in the MSH2 gene. We aimed to study the sequence of the MSH2 gene in 124 invasive C. glabrata isolates causing incident episodes of candidemia (n = 81), subsequent candidemia episodes (n = 9), endocarditis (n = 2), and in vitro-generated echinocandin-resistant isolates (n = 32) and assessed its relationship with genotypes, acquisition of antifungal resistance in vivo and in vitro, and patient prognosis. The MSH2 gene was sequenced, and isolates were genotyped using six microsatellite markers and multilocus sequence typing (MLST) based on six housekeeping genes. According to EUCAST, isolates causing candidemia (n = 90) were echinocandin susceptible, and four of them were fluconazole resistant (MIC ≥64 mg/liter). One isolate obtained from a heart valve was resistant to micafungin and anidulafungin (MICs, 2 mg/liter and 1 mg/liter, respectively). MSH2 gene mutations were present in 44.4% of the incident isolates, the most common being V239L. The presence of MSH2 mutations was not correlated with in vitro or in vivo antifungal resistance. Microsatellite and MLST revealed 27 genotypes and 17 sequence types, respectively. Fluconazole-resistant isolates were unrelated. Most MSH2 mutations were found in cluster isolates; conversely, some mutations were found in more than one genotype. No clinical differences, including previous antifungal use, were found between patients infected by wild-type MSH2 gene isolates and isolates with any point mutation. The presence of MSH2 gene mutations in C. glabrata isolates causing candidemia is not correlated with specific genotypes, the promotion of antifungal resistance, or the clinical outcome.